High Performance Computing on Vector Systems 2006 [electronic resource] : Proceedings of the High Performance Computing Center Stuttgart, March 2006 - Teraflop Workbench Project Workshop (4th : 2006 : Stuttgart, Germany); Resch, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
PSZJBL